Enhanced thermoelectric performance of Mo nanoparticle decorated n-type Bi2Te2.7Se0.3 powder composites - Lee, Sang-Seok; Jang, Injoon; Rhyee, Jong-Soo; Hong, Soon-Jik; Yoo, Sung Jong; Park, Il-Kyu (ELSEVIER, 2021)
Although thermoelectric energy conversion technology has received much attention because of its noiseless and economical operations, a low figure of merit (ZT) values of thermoelectric materials has prevented a wider variety of practical applications. Recently thermoelectric composite structures with metal or oxide nanoparticles have been widely investigated to enhance the ZT values by increasing the power factor and decreasing the thermal conductivity simultaneously. However, the difficulties in distributing the nanoparticles in the thermoelectric material matrix homogeneously have been the main problem. Herein we fabricated a thermoelectric nanocomposite structure by decorating the Mo nanoparticles on the surface of Bi2Te2.7Se0.3 powders. The Mo nanoparticles were uniformly coated on the Bi2Te2.7Se0.3 powder surface based on the sacrificial organic supporter composite consisting of Mo-coated glucose. The Mo nanoparticle/Bi2Te2.7Se0.3 composites exhibited a simultaneous decrease of thermal conductivity and electrical resistivity due to an Anderson localization effect. Therefore, the Mo nanoparticle composite structure showed enhanced ZT values by 1.31 times compared to that of bare Bi2Te2.7Se0.3 powders exhibiting a ZT value of 0.67 at 373 K.